Digital Transformation in Higher Education - Soegoto, Yudistira; Meyliana, M; Prabowo, H; Hidayanto, A Nizar; Trisetyarso, A; Pradipto, Y Dedy (Universitas Komputer Indonesia, 2023)
At this time, in the pandemic season of Covid-19, digital transformation is developing twice as fast; as usual, the organizations or institutions that are most demanded to adapt to this pandemic are universities. The purpose of this research is to identify the development of digital transformation that occurs in universities from year to year and to identify the development of digital transformations that occur based on areas in higher education using the core concepts of digital transformation and By using the systematic literature review (SLR) method, The results of this study are expected to provide insight into the development of digital transformation that occurs in higher education